PELATIHAN MANAJEMEN USAHA DAN SOLIALISASI ALAT PEMISAH BIJI SIRSAK PADA KELOMPOK UMKM “TANI HASIL KEBUN” DI PATUK, GUNUNGKIDUL - Muhammad Priya Permana; Supriyanto, Sidiq (Jurnal Abdi Insani, 2024)
Kapanewon Patuk is a part of Gunungkidul district which has great potential in cultivating soursop fruit. People have been selling products directly to traditional markets. So the sale of soursop fruit is IDR 4,000/kg, making a small income. To overcome this problem, a community service program is proposed that focuses on HR management training and socialization of production using a soursop seed separator for the MSME group "Garden Produce Farmers". This program aims to increase farmers' knowledge and skills in processing soursop fruit into frozen products with higher selling value, increasing production efficiency and quantity through the use of specially designed seed separator tools. This activity method includes 5 stages: observation, problem identification, implementation of training, creation of SOPs and job desks, and design of a soursop seed separator tool. The results of this activity make soursop fruit processing productivity more efficient. Estimates for separating soursop seeds, which initially required 15 minutes for 1 fruit, have become 15 minutes for every 5 kg of fruit. Apart from that, this tool will increase the market price from raw products to processed products. Based on the results of this activity, the community became more creative in processing the soursop fruit harvest. In addition, this activity provides added value to the soursop harvest by converting sales of raw soursop into sales of processed products.